Vanadium-Substituted Wells-Dawson Potassium Salt as Catalyst for Liquid phase Oxidation of 1,4-dihydropyridine Derivative - M. Sanchez, Laura; G. Sathicq, Angel; T. Baronetti, Graciela; J. Thomas, Horacio (Current Catalysis, 2014)
Dawson-type heteropolyoxometalate compounds (HPC) P2M18O62 -6 (M= Mo, W) have received increasing attention in the catalytic field due to the combination of redox and acidic properties in the same structure. It has been proved that the introduction of vanadium into the Keggin framework is beneficial for redox catalysis, shifting its activity from acid to redox-dominated. In this work we prepared and characterized vanadium (V) substituted Wells-Dawson heteropolysalt (WDKV). Fresh solid samples were characterized by 31P MAS-NMR, FTIR, SEM, XRD, TGA and Potentiometric titration measurements. Also, we performed the oxidation of a 1,4-dihydropyridine using WDKV as catalyst in acetonitrile media, with H2O2 as oxidant agent. The optimal procedure is the following: 1 mmol% of WDKV, a ratio 1,4-DHP: H2O2 (1:214) at reflux of acetonitrile. It must be noted that along all reactions, no secondary products were observed.
Keywords: Oxidation